Mining Gut Microbiota From Bariatric Surgery for MAFLD - Wu, Wei-Kai; Chen, Yi-Hsun; Lee, Po-Chu; Yang, Po-Jen; Chang, Chin-Chen; Liu, Kao-Lang; Hsu, Cheng-Chih; Huang, Chi-Chang; Chuang, Hsiao-Li; Sheen, Lee-Yan; Liu, Chun-Jen; Wu, Ming-Shiang (Frontiers in Endocrinology, 2021)
The progression of metabolic dysfunction associated fatty liver disease (MAFLD) leads to steatohepatitis, liver fibrosis and hepatocellular carcinoma. Thus far, there have been no FDA-approved medications for MAFLD. Bariatric surgery (BS) has been found to improve insulin resistance, steatohepatitis and liver fibrosis but is not recommended for treating MAFLD due to its invasiveness. Recent studies suggest the improved glucose metabolism after BS is a result of, at least partly, alterations to the gut microbiota and its associated metabolites, including short chain fatty acids and bile acids. It makes sense the improved steatohepatitis and fibrosis after BS are also induced by the gut microbiota that involves in host metabolic modulation, for example, through altering bile acids composition. Given that the gut–liver axis is a path that may harbor unexplored mechanisms behind MAFLD, we review current literatures about disentangling the metabolic benefits of MAFLD after BS, with a focus on gut microbiota. Some useful research tools including the rodent BS model, the multiomics approach, and the human microbiota associated (HMA) mice are presented and discussed. We believe, by taking advantage of these modern translational tools, researchers will uncover microbiota related pathways to serve as potential therapeutic targets for treating MAFLD.